Strategi Pelestarian Tradisi Makepung Berbasis Pariwisata Budaya Berkelanjutan di Kabupaten Jembrana - Ni Putu Eva Samiastika Yanthi; I Nyoman Yoga Segara; Made Iwan Indrawan Jendra (Jayapangus Press, 2026)
The Makepung tradition is a cultural heritage of Jembrana Regency with the potential to support sustainable tourism; however, its sustainability is threatened by low participant regeneration, high maintenance costs, and the impacts of agricultural modernization. This research aims to analyze the preservation condition of the Makepung tradition, identify the internal and external factors influencing it, and formulate a preservation strategy based on sustainable cultural tourism. This study employs a descriptive qualitative approach, collecting data through observation, in-depth interviews, and documentation, followed by analysis using the Miles and Huberman interactive model and SWOT analysis. The matrix analysis results indicate an IFAS score of 2.82 and an EFAS score of 2.74, placing this tradition in the SO (Strength-Opportunity) strategy position. Based on this position, an integrated preservation strategy model is formulated resting on five main pillars: (1) cultural value preservation, (2) community empowerment, (3) institutional strengthening, (4) sustainable cultural tourism development, and (5) local economic sustainability strengthening through multi-stakeholder collaboration. In conclusion, implementing this collaborative and integrated preservation strategy not only safeguards the local cultural heritage from extinction but also has the potential to enhance the competitiveness of Jembrana Regency as a sustainable cultural tourism destination.